Ski Inhibits TGF-β/phospho-Smad3 Signaling and Accelerates Hypertrophic Differentiation in Chondrocytes - Kim, Kyung-Ok (2012)
Since TGF-β/Smad signaling inhibits chondrocyte maturation, endogenous negative regulators of TGF-β signaling are likely also important regulators of the chondrocyte differentiation process. One such negative regulator, Ski, is an oncoprotein that is known to inhibit TGF-β/Smad3 signaling via its interaction with phospho-Smad3 and recruitment of histone deacetylases (HDACs) to the DNA binding complex. Based on this, we hypothesized that Ski inhibits TGF-β signaling and accelerates maturation in chondrocytes via recruitment of HDACs to transcriptional complexes containing Smads. We tested this hypothesis in chick upper sternal chondrocytes (USCs), where gain and loss of Ski expression experiments were performed. Over-expression of Ski not only reversed the inhibitory effect of TGF-β on the expression of hypertrophic marker genes such as type × collagen (colX) and osteocalcin, it induced these genes basally as well. Conversely, knockdown of Ski by RNA interference led to a reduction of colX and osteocalcin expression under basal conditions. Furthermore, Ski blocked TGF-β induction of cyclinD1 and caused a basal up-regulation of Runx2, consistent with the observed acceleration of hypertrophy. Regarding mechanism, not only does Ski associate with phospho-Smad2 and 3, but its association with phospho-Smad3 is required for recruitment of HDAC4 and 5. Implicating this recruitment of HDACs in the phenotypic effects of Ski in chondrocytes, the HDAC inhibitor SAHA reversed the up-regulation of colX and osteocalcin in Ski over-expressing cells. These results suggest that inhibition of TGF-β signaling by Ski, which involves its association with phospho-Smad3 and recruitment of HDAC4 and 5, leads to accelerated chondrocyte differentiation.